The resolution of problems in the world of the company. Exploratory study on decisional relativismo - Acevedo Borrego, Adolfo (2009)
In the world of organizations, there are unwanted problematic situations based on principles not discussed but established in practice: making decisions based on concepts and pre-defined paradigms. This approach improves one aspect of the problem, but creates failures in other aspects, which becomes potentially even more serious problems. There are conceptual differences between making decisions and solving problems. The perception of complex problems begins with the identification of holistic elements of the organization: structural, process, human and change dimensions. Problem solving considers three elements: 1) defining the level of resolution or solver position, 2) choice of decision criteria or dimensions relevant, 3) choice of study, formulation and solution tools.